Detection of IL-8 in human serum using surface-enhanced Raman scattering coupled with highly-branched gold nanoparticles and gold nanocages - Wang, Zhen-yu; Li, Wei; Gong, Zheng; Sun, Pei-rong; Zhou, Tong; Cao, Xiao-wei (New journal of chemistry, 2019)
Interleukin 8 is known as an important chemokine and plays an important role in tumor growth and angiogenesis. Over expression of IL-8 has been detected in a variety of human tumors, including gastric cancer and breast cancer. Therefore, the development of rapid and sensitive profiling methods is crucial for evaluating the level of IL-8 expression in human serum, which is related to normal and tumor states. In our study, surface-enhanced Raman scattering (SERS) based on the double antibody sandwich format is reported for the determination of IL-8. Highly-branched gold nanoparticle (HGNP) substrates were fabricated and conjugated with anti-IL-8 (coating) as capturing substrates, and gold nanocages (GNCs) adsorbed with 4-mercaptobenzoic acid are modified with anti-IL-8 (labeling) as SERS tags. After the substrates captured IL-8, the SERS tags were bonded to the captured IL-8. The interaction of the SERS capturing substrates (HGNPs) and the SERS tags (GNCs) shows high sensitivity and a low detection limit for IL-8. The linear dynamic range of SERS for IL-8 was from 10 pg mL −1 to 1 μg mL −1 , which shows a linear relationship between IL-8 concentration and SERS intensity. The detection limit was 6.04 pg mL −1 in phosphate buffered saline and 6.88 pg mL −1 in human serum. The analysis results of serum samples obtained from healthy subjects and two different types of cancer patients (breast cancer and gastric cancer) by using the SERS method were acceptably consistent with those obtained by the enzyme-linked immunosorbent assay. The proposed immunoassay shows great potential for application in clinical diagnosis. Surface-enhanced Raman scattering (SERS) based on the double antibody sandwich format was used for the determination of IL-8.